A QUALITATIVE RESEARCH ANALYSING NON-FINANCIAL INCENTIVES TOWARD EMPLOYEE PERFORMANCE AT IBIS MANADO CITY CENTER BOULEVARD - Karwur, Karina Ocktovenisia; Lambey, Linda .; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Employee will sustain high levels of performance if they are appreciated and rewarded accordingly. Moreover, through incentives reward, the management of Ibis Manado City Center Boulevard Hotel expects the employee to be more passionate to achieve the categories of reward in line with enhancing their performance as well. Financial incentives if not assisted by other types of incentives, are not sufficient and only can boost employee performance at the moment. On the other hand, non-financial incentives seen more effective motivators that can fulfill the intrinsic motivational for the employees to enhance their performance. Hence, the focus of this research is the effect of non-financial incentives towards employee performance. Used qualitative methods, 10 employees of Ibis Manado City Center Boulevard Hotel were interviewed to collect the data. Results show that job-related incentives have the most pivotal role in enhancing employee performance at work. Management should give chance to every employee to received job-related incentives since according to findings it really helpful for their daily work and also career.Keywords: non-financial incentives, employee performance, job-related incentives.